Determinants of the Behavior of Hotel Employees on the Use of Personal Protective Equipment (PPE) at Simalungun City Hotel - Yulia Delfahedah (PT Inovasi Pratama Internasional, 2022)
The use of Personal Protective Equipment (PPE) is the final stage of the hazard control method. However, the use of PPE will be very important if the technical and administrative controls that have been carried out optimally before still have a relatively high hazard potential. The benefits of using PPE while working are enormous in preventing work accidents, but in reality there are still many workers who do not use PPE properly and in accordance with the potential hazards while working At Simalungun City Hotel in 2022, the number of employees using PPE was only 14 employees (16 7%) This type of research is an analytic research using a cross sectional design. The number of samples used were all Simalungun City Hotel employees, namely 84 people. The results showed that 70 employees (83.3%) did not use PPE, 64 employees had low education, 74 employees (88.1%) had a new working period, 56 employees (66.7%) have good knowledge, 26 employees (31%) have sufficient PPE availability. Suggestions from this study are to increase worker awareness regarding the use of PPE, potential hazards in the workplace and awareness of the importance of maintaining safety and health at work. In addition, companies are expected to tighten supervision on the use of PPE and provide rewards or punishments related to the use of PPE at work.